Austronea oblongifolia (Hyacinthaceae subfam. Urgineoideae), a new species from the Eastern Cape Province in South Africa - Martínez-Azorín, Mario; Dold, Anthony P.; Crespo, Manuel B.; Vargas, María Ángeles Alonso (Phytotaxa, 2023)
Our field work in the Eastern Cape Province of South Africa revealed an undescribed species of Austronea, which approaches A. marginata and related species, but differs in distinct morphological characters and distribution. We here describe Austronea oblongifolia to include plants showing bulbs with compact scales; a single, oblong, apiculate leaf that is appressed to the ground, and is minutely scabridulous on the upper surface with undifferentiated leaf margin; inflorescence subcapitate with a short peduncle; lowermost bracts with a broad spur; and reddish flowers with smooth filaments. We provide a complete morphological description, as well as data on ecology and distribution.